Knowledge and attitude toward glaucoma among relatives of patients with established disease: a cross-sectional study at a tertiary eye care center - Patel, Deepak; Kumar, Nishant (International Journal of Research in Medical Sciences, 2025)
Background: Glaucoma is a leading cause of irreversible blindness worldwide. Relatives of glaucoma patients are at higher risk, yet their awareness and attitude toward the disease are often insufficient. The aim of the study was to assess the knowledge and attitude regarding glaucoma among first-degree relatives of patients attending a tertiary eye care center in India. Methods: A cross-sectional study was conducted over six months at (tertiary eye care center). Two hundred fifty first-degree relatives of patients diagnosed with primary glaucoma were recruited. A structured, validated questionnaire assessed knowledge of glaucoma, risk factors, symptoms, and attitudes toward screening. Descriptive statistics and Chi-square tests were applied. Results: Among 250 participants, 38% knew that glaucoma could cause irreversible blindness, and 45% recognized family history as a risk factor. Only 28% had previously undergone eye screening. Positive attitudes toward regular screening were observed in 52%. Higher education and prior exposure to glaucoma information were significantly associated with better knowledge and attitudes (p<0.05). Siblings of glaucoma patients showed higher awareness and more positive attitudes than parents or children. Younger participants (<40 years) demonstrated slightly better knowledge, though differences were not statistically significant. Conclusions: Despite increased risk, knowledge and screening behavior among relatives remain suboptimal. Structured educational programs and targeted interventions in tertiary centers are essential to enhance awareness and early detection of glaucoma.